A novel mutation in DAX1 causes delayed-onset adrenal insufficiency and incomplete hypogonadotropic hypogonadism - Tabarin, Antoine (American Society for Clinical Investigation, 2000)
Mutations in the DAX1 gene cause X-linked adrenal hypoplasia congenita (AHC) and hypogonadotropic hypogonadism (HHG). In affected boys, primary adrenal insufficiency occurs soon after birth or during early childhood; HHG is recognized at the expected time of puberty. In this report, we describe the novel phenotype of a man who presented with apparently isolated adrenal insufficiency at 28 years of age. Examination revealed partial pubertal development and undiagnosed incomplete HHG. Gonadotropin therapy did not improve his marked oligospermia, suggesting a concomitant primary testicular abnormality. Genomic analysis revealed a novel missense mutation, I439S, in DAX1. The mutant DAX-1 protein was studied for its ability to function as a transcriptional repressor of target genes. Consistent with the patient’s mild clinical phenotype, the I439S mutation conferred intermediate levels of repressor activity of DAX-1 when compared with mutations associated with classic AHC. This unique case extends the clinical spectrum of AHC to include delayed-onset primary adrenal insufficiency in adulthood and milder forms of HHG. Furthermore, in accordance with findings in Ahch (Dax1) knockout mice, the clinical features in this patient suggest that DAX-1 function is required for spermatogenesis in humans, independent of its known effects on gonadotropin production.